ENCORE Enhanced Code Galileo Receiver for Land Management Applications in Brazil - Silva, Pedro F.; Silva, Joao S.; Peres, Tiago; Barbin, Silvio E.; Diez, Jose; Palomo, Jose; Galera Monico, Joao F. [UNESP]; Camargo, Paulo O. [UNESP]; Colomina, Ismael; Pares, Eulalia; Granemann, Emerson Z.; Freitas, Eduardo; et al. (Ieee, 2010)
Taking benefit of the new Galileo ranging signals, the ENCORE (Enhanced Code Galileo Receiver) project aims to develop a low-cost Land Management Application to cover needs of the Brazilian market in terms of geo-referencing and rural/urban cadastre, using a low-cost Enhanced Galileo Code Receiver as baseline. Land management applications require precision and accuracy levels from a few to several decimetres that are under-met with current pseudorange-based receiver and over-met with phase observations. This situation leads either to a waste of resources, or to lack of accuracy. In this project, it is proposed to fill this gap using the new possibilities of the Galileo ranging signals, in particular E5 AltBOC and E1 CBOC. This approach reduces the cost of the end-user solution, helping the rapid penetration of Galileo technology outside Europe
Keywords: GNSS; Galileo; AltBOC; Land Management